Implementasi Metode Six Sigma DMAIC Untuk Menurunkan Defect Pada Back End Frame 2TYGY (Jurnal Ilmiah Teknik Mesin, 2026)
This study aims to reduce defects in the Back End Frame 2TYGY product at PT XYZ using the Six Sigma DMAIC method. Production data of 87,166 units and 6,426 defects (June 2024 – May 2025) showed an initial defect rate of 7.45%, with Blowhole Welding (48.2%) and Pipe Not Centre (20.5%) contributing 68.7% of total defects. Pareto, Fishbone, and 5 Why analyses identified root causes in welding current variation and worn jigs. FMEA proposed weekly calibration, new jigs, current sensors, and operator training. DMAIC implementation reduced defect rate by 42.6% to 4.28%, DPMO by 59.6% from 18,425 to 7,450, increased Sigma Level by 12.5% to 4.05, and saved rework costs by 54.2% (IDR 650 million/year). The results support sustainable quality control in the automotive industry. Keywords: Six Sigma, DMAIC, Defect Reduction, Welding Quality, FMEA